2012
DOI: 10.1021/jm201528b
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-1-Selective Inhibitors Based on the (E)-2′-Des-methyl-sulindac Sulfide Scaffold

Abstract: Prostaglandins (PGs) are powerful lipid mediators in many physiological and pathophysiological responses. They are produced by oxidation of arachidonic acid (AA) by cyclooxygenases (COX-1 and COX-2) followed by metabolism of endoperoxide intermediates by terminal PG synthases. PG biosynthesis is inhibited by nonsteroidal anti-inflammatory drugs (NSAIDs). Specific inhibition of COX-2 has been extensively investigated, but relatively few COX-1-selective inhibitors have been described. Recent reports of a possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
55
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 77 publications
(186 reference statements)
3
55
0
Order By: Relevance
“…The inhibition of COX-2 and iNOS expression has been shown to suppress the development of skin tumor [32]. Previous report stated that sulindac, a specific inhibitors for COX-1/COX-2 expression that may reduce prostaglandin production leads to the inhibition of UVB-induced skin cancer [33]. Our results also clearly mentioned that administration of morin significantly inhibited UVB-induced overexpression of COX-2 and iNOS in mouse skin.…”
Section: Discussionsupporting
confidence: 80%
“…The inhibition of COX-2 and iNOS expression has been shown to suppress the development of skin tumor [32]. Previous report stated that sulindac, a specific inhibitors for COX-1/COX-2 expression that may reduce prostaglandin production leads to the inhibition of UVB-induced skin cancer [33]. Our results also clearly mentioned that administration of morin significantly inhibited UVB-induced overexpression of COX-2 and iNOS in mouse skin.…”
Section: Discussionsupporting
confidence: 80%
“…Involvement of COX-1, in the pathophysiology of diseases, such as pain, fever, analgesia, neuroinflammation and cancer is based on both preclinical and clinical reports proposing COX-1 as a potential therapeutic target [6]. Thus, involvement of COX-1, rather than COX-2, in carcinogenesis has been demonstrated emphatically in ovarian and breast human cancers [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Potent inhibitors of TXS display a key cationinteraction with the iron atom from heme group present in the enzyme catalytic site. This interaction is well-known in literature [53][54][55] specially for imidazole-or 3-pyridine-based inhibitors 52,56 . Accordingly, our results revealed that the phenyl ring in 3a, 3b and 3h derivatives oriented toward the heme group establish a feasible cation-interaction with the heme iron.…”
Section: Discussionmentioning
confidence: 97%